Sarcomatoid carcinoma transformation in oral undifferentiated carcinoma following sequential immune combined targeted therapy: a case report - Li, Jieying; Zhan, Xiaohong; Shang, Wei; Song, Kai (Frontiers in Immunology, 2024)
The diagnosis and treatment of head and neck undifferentiated carcinoma (HNUC) present significant challenges. Herein, we present the case of a patient with advanced HNUC who underwent conversion surgery following treatment with a combination of pembrolizumab and nimotuzumab.During therapy, histological transformation from undifferentiated to sarcomatoid carcinoma was detected at the primary site. This case not only highlights the potential of immune combinationtargeted therapy to reduce tumour burden and increase the surgical options for patients, but also reveals the complex alterations in tumour biology that may occur during treatment. It emphasizes the necessity for routine pathological assessments throughout the therapeutic regimen to guide personalised therapeutic strategies and optimise patient prognoses.